2020
DOI: 10.3390/pharmaceutics12070644
|View full text |Cite
|
Sign up to set email alerts
|

Acemannan Used as an Implantable Biomaterial for Vital Pulp Therapy of Immature Permanent Teeth Induced Continued Root Formation

Abstract: Direct pulp-capping, a vital pulp therapy, is used to protect and preserve pulp vitality by applying a biomaterial on the pulp exposure site. Acemannan, a polysaccharide extracted from Aloe vera, induces osteodentin-bridge formation to cover the exposure site in vivo. We evaluated the effect of acemannan sponges on partial pulpotomized permanent teeth with caries or accident-induced pulp exposure (n = 50). After removing infected dentin and inflamed pulp tissue, the teeth were randomly divided into ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…Immature permanent teeth present a fragile root with open apices. The primary aim of vital pulp treatment of these teeth is to ensure the complete root apex formation and reinforcing the root walls [ 45 , 49 ]. Pulpotomy, a type of VPT, is considered the suitable procedure for an immature permanent tooth with exposed pulp due to a deep caries or trauma [ 8 , 9 , 10 , 11 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immature permanent teeth present a fragile root with open apices. The primary aim of vital pulp treatment of these teeth is to ensure the complete root apex formation and reinforcing the root walls [ 45 , 49 ]. Pulpotomy, a type of VPT, is considered the suitable procedure for an immature permanent tooth with exposed pulp due to a deep caries or trauma [ 8 , 9 , 10 , 11 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In animal and clinical studies, acemannan induced osteo-dentin bridge formation with vital pulp tissue beneath it [10,11]. Therefore, acemannan would be an alternative implantable biomaterial to promote pulp healing for vital pulp therapy similar to MTA and Biodentin [12].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium hydroxide (Ca(OH) 2 ) has been considered the "gold standard" of direct pulp capping materials in permanent teeth, against which new materials should be tested although a wide variety of materials have been used for direct pulp capping. 68,253,254 Pulp-capping clinical studies have shown equal 255 or more successful results for the calcium silicate cements compared to calcium hydroxide dressings. 102,104,[256][257][258][259][260] Calcium hydroxide itself does not set, unlike the calcium silicate cement products.…”
Section: Pulp Tissue Treatmentsmentioning
confidence: 99%